Review of American Idle: Late-Career Job Loss in a Neoliberal Era - Katz, Stephen (Age, Culture, Humanities: An Interdisciplinary Journal, 2026)
A review of American Idle: Late-Career Job Loss in a Neoliberal Era, by Annette Nierobisz and Dana Sawchuk. New Brunswick: Rutgers University Press, 2025.